An Analysis of Teacher Talk used by English Teacher at SMKN 5 Samarinda - Siti Aminah; Dedi Rahman Nur; Ariyanti Ariyanti (Borneo Educational Journal (Borju), 2019)
This research used qualitative research method. The research design of this study is descriptive study. The researcher used interview as the instruments. The participants in this study were teachers of SMK Negeri 5 Samarinda and the researcher took three teachers. The research used purpose sampling technique. In this research the data collection techniques is using interviews to find out the types of teacher talk and the reasons for the teacher used teacher talk. The findings showed that there are three teachers talk used by teacher such as asking question, lecturing and giving direction. Nevertheless, there are three main reasons for the teacher used the teacher talk such as students’ language ability, students’ motivation and students’ participation.